Penerapan Digital Marketing Sebagai Strategi Pemasaran pada UMKM di Kelurahan Turi, Kecamatan Sukorejo, Kota Blitar. - Nicolas, Diva Delia Rossa; Imaningsih, Niniek; Fadil, Cholid (Jurnal Ilmiah Wahana Pendidikan, 2023)
The development of the current era is very fast where all information can be searched via the internet. Making people's habits a lot of changes and more practical. As a business person adapting to changing times is not easy. There needs to be a place to develop knowledge and skills in implementing digitalization, especially in marketing. This activity is carried out so that business people can adapt so that the MSMEs that are run will further develop. The research method was carried out in five stages, namely by conducting a survey of MSMEs using interviews, outreach, re-branding, product photo assistance, and assistance in creating social media and e-commerce. The target of this research Frozen Food Lancar Jaya, Batik Kembang Turi, dan Arum Snack MSME’s. With this research, it is hoped that MSMEs can compete with competitors and the target market can expand not only in the Turi sub-district but can reach all of Indonesia